Consequences of Androctonus mauretanicus and Buthus occitanus scorpion venoms on electrolyte levels in rabbits - Khadija Daoudi; Fatima Chgoury; Myriam Rezzak; Oussama Bourouah; Lotfi Boussadda; Abdelaziz Soukri; Jean-Marc Sabatier; Naoual Oukkache (Heliyon, 2017)
Androctonus mauretanicus (A. mauretanicus) and Buthus occitanus (B. occitanus) scorpions, which belong to the Buthidae family, are the most venomous scorpions in Morocco. For the first time, we investigated the effects of such scorpion venoms on serum electrolytes in subcutaneously injected rabbits. For this purpose, 3 groups of 6 albinos adult male rabbits (New Zealand) were used in this experiment. Two of the groups were given a single subcutaneous injection of either crude Am venom (5 μg/kg) or Bo venom (8 μg/kg) whereas the third group (control group) only received physiological saline solution (NaCl 0.9%). The blood samples were collected from injected rabbits via the marginal vein at time intervals of 30 min, 1 h, 2 h, 4 h, 6 h and 24 h after venom injection. The concentrations of electrolytes in the serum samples were measured. Our study indicates that scorpion envenomation in vivo, rabbit animal model, caused severe and persistent hypomagnesaemia and hypochloremia, which are accompanied of hypernatremia, hyperkalemia and hypercalcaemia. The intensity of electrolytes imbalance was clearly superior in the case of A. mauretanicus scorpion venom (although a lower quantity of venom was injected). This is coherent with the experimental data which indicate that A. mauretanicus venom is more toxic than B. occitanus venom.